Navigating the digital landscape: situation and risk assessment of digital solutions in forwarding companies - Lapinskaitė, Indrė; Ingaunytė, Neda; Zemlickienė, Vaida; Martinkutė-Kaulienė, Raimonda (Technological and Economic Development of Economy, 2024)
This research emphasises the transformative power of digital solutions in Lithuanian forwarding companies, addressing the necessity for a systematic risk assessment to optimise processes and mitigate associated risks. The survey indicates an increasing adoption of digital solutions, with around two-thirds of companies already utilising them. A case study employing the AHP method identifies three key digital solutions: invoice automation, waybill digitisation and blockchain. A combined solution called a “document flow and management system”, showed significant potential for time and cost savings. Three risks – synchronising participants, employee resistance, and a lack of specialists – are identified as having the highest overall assessment and were selected for further analysis while implementing the prioritised digital solution. The expert evaluation identifies employee resistance as the most probable risk, posing potential significant losses in the initial post-implementation phase. Although issues with synchronising participants could yield similar losses, experts view this risk as less probable than employee resistance. After the AHP analysis, it was decided to evaluate the current information and document flow process, in other words, to optimise the process. The optimisation results show that freight forwarding companies could reduce document management time by up to 59%.